ANALYSIS OF INVESTMENT DECISIONS, FUNDING DECISIONS, AND DIVIDEND POLICIES ON THE PROFITABILITY OF THE INFRASTRUCTURE SECTOR ON THE INDONESIA STOCK EXCHANGE - Rifai, Rahmat Hidayat (Ridwan Institute, 2024)
This study aims to analyze the influence of investment decisions, funding decisions, and dividend policies on the profitability of infrastructure sector companies on the Indonesia Stock Exchange, both individually and together. The qualitative and quantitative data were collected using secondary data from the financial statements of Infrastructure sector companies taken from the Jakarta Stock Exchange website for the period 2018-2021. The results show that investment decisions have a positive but not significant influence on the profit margin of the infrastructure sector company. The dividend policy has a negative and insignificant effect on the profits of the company. Therefore, the higher the company's commitment to distributing dividends, the better the profitability will be encouraged. Based on the results of the study, it is recommended that the management of infrastructure sectors manage investment decisions and funding policies efficiently to increase profitability and competitiveness.